2018
DOI: 10.1016/j.hrthm.2018.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Accelerometer-based atrioventricular synchronous pacing with a ventricular leadless pacemaker: Results from the Micra atrioventricular feasibility studies

Abstract: Accelerometer-based atrial sensing is feasible and significantly improves AVS in patients with AV block and a single-chamber leadless pacemaker implanted in the right ventricle.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
128
0
8

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(138 citation statements)
references
References 19 publications
2
128
0
8
Order By: Relevance
“…However, as the LP is currently only available as a single-chamber right ventricular device, this approach could potentially be limited to a single-chamber pacemaker population. Future concepts, such as leadless VDD resulting in atrioventricular synchronous pacing [59, 60], might broaden this patient population.…”
Section: Discussionmentioning
confidence: 99%
“…However, as the LP is currently only available as a single-chamber right ventricular device, this approach could potentially be limited to a single-chamber pacemaker population. Future concepts, such as leadless VDD resulting in atrioventricular synchronous pacing [59, 60], might broaden this patient population.…”
Section: Discussionmentioning
confidence: 99%
“…Current clinical trials of commercially available leadless pacemakers, such as Micra (Medtronic, Minneapolis, MN), have shown their effectiveness in single‐chamber pacing but lack CRT capabilities. A recent study demonstrated the clinical efficacy of using far‐field atrial sensing toward achieving AV synchrony in patients using the Micra device . However, even such an innovative approach cannot provide options for multichamber pacing using the current iterations of wireless pacemakers.…”
Section: Discussionmentioning
confidence: 99%
“…Sudden cardiac death · Subcutaneous defibrillator · Leadless pacemaker · His bundle pacing · Implant infections [12]. Dies wurde in der kürzlich publizierten MARVEL2-Studie bestätigt [13].…”
Section: Introductionunclassified